Spectral properties of conservative, dispersive, and absorptive photonic crystals. Issue 3 (21st September 2018) - Engström, Christian; Torshage, Axel
Abstract : This article reviews both recent progress on the mathematics of dispersive and absorptive photonic crystals and well‐established results on conservative photonic crystals. The focus is on properties of the photonic band structures and we also provide results that are of importance for the understanding of lossy metal‐dielectric photonic crystals.